Advanced Methods of Bank Risk Management - Kolesnik, Ya. V. (Statistics of Ukraine, 2021)
Main approaches to building up a system for management of financial risks faced by banks are discussed. It is shown that risk management in banking is a complex process aimed at identification of risk sources, assessment and minimization of the effects of the identified risks, in order to reduce their adverse impact on the commercial bank performance. The main objective of banks is defined as maintaining the constant balance between the needs in resources and the capabilities of their acquisition. The importance and necessity of measurement and quantification of the level of specific types of risk and/or the cumulative risk is highlighted. Special emphasis is made on the credit risk caused by the probability of bank counterparties’ failure to fulfill their obligations. Its usual consequence is failure to repay (fully or partially) the debt principal and the interests in terms specified by the contract. It is shown that the level of credit risk in a country is conditional on macro- and microeconomic factors, with highlighting their effects. It is demonstrated that the adverse impact of inflation is the most explicit one, as it provokes devaluation of bank assets which major share is funds and financial investment. Functional risks are caused by subjective and objective factors, and by system failures, and they cover strategic risks related with mistakes in strategic management. Financial risks can trigger unpredictable change in the amount, profitability and structure of bank assets and liabilities. The liquidity risk can occur when a bank has insufficient or surplus liquidity. The insufficient liquidity can provoke bank insolvency. The inflation risk has ambiguous effects for bank operation. The successful risk management is a critically important condition for competitiveness and reliability of any financial organization; its objective is to identify and prevent potential adverse events, and to find the tools for minimization of their effects as part of the elaborated methodology of management. Further research devoted to problems of risks faced by the Ukrainian banking system and economic analysis of specific risks will help outline the ways of cost reduction in the banking sector and constantly extend the range of bank services.